Tech & Talk: Enhancing Teaching with Technology and English - Dangin; Heribertus Binawan; Istianatul Hikmah (International Journal Of Community Service, 2025)
International schools partnering in the "Tech & Talk" program face challenges in actively using English and integrating technology into teaching. Although teachers have a basic understanding of English, they often struggle with spontaneous communication, clear instructions, and interactive discussions, which can lead to a passive learning environment. Despite having access to digital devices, many educators hesitate to use them effectively due to unfamiliarity or lack of training. Traditional teaching methods still dominate, limiting the potential of technology to create engaging and student-centered learning experiences. The "Tech & Talk" program aims to address these issues through practical workshops, increase teachers' confidence in using English for classroom interactions, and encourage them with practical digital teaching strategies. By enhancing language skills and technological proficiency, the program aims to accelerate a more dynamic and efficient learning environment.